Penguatan Pengetahuan Ibu tentang ASI Eksklusif untuk Mencegah Stunting pada Balita di Puskesmas Rawang Panca Arga - Sartika, Cut Dewi; Pohan, Meilisya; Mahyunidar (Cattleya Darmaya Fortuna, 2025)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition, resulting in children being shorter than their age. Malnutrition occurs while the baby is in the womb and in early life after birth, but appears in children aged 2 years or the first 1000 days of life (HPK). 1000 HPK is a phase of life that begins from the formation of the fetus in the womb (270 days) until the child is 2 years old (730 days) (Hidayah, et al., 2021). Research Objective: To determine the relationship between exclusive breastfeeding in toddlers and the incidence of stunting at the Rawang Panca Arga Community Health Center in 2024. The observational counseling method with a retrospective cohort study counseling design is analytical. The retrospective cohort study follows subjects/patients who first entered the Community Health Center until they recover or not. This counseling uses patient medical records for one year at the Rawang Panca Arga Community Health Center. Data analysis was carried out using univariate and bivariate with the chi-square test. Results: The results of the Chi-Square test analysis showed a p value of 0.026 (p < α 0.05).which means that there is a significant relationship between exclusive breastfeeding and the incidence of stunting at the Rawang Panca Arga Community Health Center in 2024. Conclusion: There is a significant relationship between giving Exclusive breastfeeding with the incidence of stunting in toddlers at the Rawang Panca Arga Community Health Center in 2024, with a p value = 0.026 (p<0.05).